Leaders’ Moral Competence and Employee Outcomes: The Effects of Psychological Empowerment and Person–Supervisor Fit - Kim, Tae-Yeol; Kim, Minsoo (2013)
This study examined how leaders’ moral competence is linked to employees’ task performance and organizational citizenship behaviors. Based on a sample of 102 employee–supervisor pairs from seven organizations in South Korea, the results of this study revealed that leaders’ moral competence was positively associated with employees’ task performance and organizational citizenship behaviors toward leaders (OCBS). As expected, employees’ psychological empowerment partially mediated the relationship between leaders’ moral competence and employees’ task performance and OCBS. Furthermore, person–supervisor fit (PS fit) moderated the relationship between leaders’ moral competence and employees’ psychological empowerment such that the relationships became stronger for individuals higher rather than lower in PS fit.
Keywords: Person–supervisor fit; Task Performance; Organizational citizenship behaviors; Psychological empowerment; moral competence